ANALISIS KARATERISTIK INDIVIDU, KARATERISTIK PEKERJAAN DAN KARATERISTIK ORGANISASI TERHADAP PRESTASI KERJA - Deni Widyo Prasetyo; Sumarji Sumarji (Universitas Islam Kadiri, 2020)
Human Resource Management Problems lately talked about and position becomes very important in terms of employee productivity. Because essentially HRM, an integration effort of personnel needs with organizational goals. showed that motivation is very important in the company. For this reason, among others, interesting authors to conduct research and compile the results of this study with the title: